Disease Severity and Perinatal Outcomes of Pregnant Patients With Coronavirus Disease 2019 (COVID-19) - Metz, Torri D. (Obstet Gynecol, 2021)
To describe coronavirus disease 2019 (COVID-19) severity in pregnant patients and evaluate the association between disease severity and perinatal outcomes. METHODS: We conducted an observational cohort study of all pregnant patients with a singleton gestation and a positive test result for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) who delivered at 1 of 33 U.S. hospitals in 14 states from March 1 to July 31, 2020. Disease severity was classified by National Institutes of Health criteria. Maternal, fetal, and neonatal outcomes were abstracted by centrally trained and certified perinatal research staff. We evaluated trends in maternal characteristics and outcomes across COVID-19 severity classes and associations between severity and outcomes by multivariable modeling. RESULTS: A total of 1,219 patients were included: 47% asymptomatic, 27% mild, 14% moderate, 8% severe, 4% critical. Overall, 53% were Hispanic; there was no trend in race–ethnicity distribution by disease severity. Those with more severe illness had older mean age, higher median body mass index, and pre-existing medical comorbidities. Four maternal deaths (0.3%) were attributed to COVID-19. Frequency of perinatal death or a positive neonatal SARS-CoV-2 test result did not differ by severity. Adverse perinatal outcomes were more frequent among patients with more severe illness, including 6% (95% CI 2–11%) incidence of venous thromboembolism among those with severe–critical illness compared with 0.2% in mild–moderate and 0% in asymptomatic (P<.001 for trend across severity). In adjusted analyses, severe–critical COVID-19 was associated with increased risk of cesarean birth (59.6% vs 34.0%, adjusted relative risk [aRR] 1.57, 95% CI 1.30–1.90), hypertensive disorders of pregnancy (40.4% vs 18.8%, aRR 1.61, 95% CI 1.18–2.20), and preterm birth (41.8% vs 11.9%, aRR 3.53, 95% CI 2.42–5.14) compared with asymptomatic patients. Mild–moderate COVID-19 was not associated with adverse perinatal outcomes compared with asymptomatic patients. CONCLUSION: Compared with pregnant patients with SARS-CoV-2 infection without symptoms, those with severe–critical COVID-19, but not those with mild–moderate COVID-19, were at increased risk of perinatal complications.